Analisis Pentingnya Harga, Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pelanggan - Jefry Leonardo; Nurmaidah Ginting; Jacky Laidy; Marcelino Dustin; Angeline Tannia; Firmansyah Firmansyah (IPM2KPE, 2023)
This research aims to test and analyze the influence of pricing, product quality and service quality on purchasing decisions. The research method used is quantitative and the type of research is descriptive and the nature of the research is explanatory research. The research results obtained that partially and simultaneously Pricing, Product Quality and Service Quality have a significant effect on Purchasing Decisions. In conclusion, the better the pricing, product quality and service quality, the better the level of purchasing decisions. Keywords: Price, Purchase Decision, Service, Product